Integrasi Pembangunan Infrastruktur Air dan Pengembangan UMKM sebagai Strategi Peningkatan Kesejahteraan Masyarakat Desa Munjuk Sempurna, Kabupaten Lampung Selatan - Farida Juwita; Husna Purnama; Maria Elina; Epi Parela (CV. Tripe Konsultan, 2025)
Sustainable village development requires an integrated approach between strengthening the productive sector and meeting the basic needs of the community. Munjuk Sempurna Village, South Lampung Regency, has great potential in the agricultural sector and Micro, Small, and Medium Enterprises (MSMEs), particularly the local food-based snack industry. However, the development of these two sectors still faces major obstacles in the form of limited access to irrigation water and weak MSME business capacity. This article aims to examine the integration of borehole development as a source of irrigation water for rice fields with the development of rengginang MSMEs as a strategy to improve the welfare of the village community. The methods used include field surveys, observations, interviews with farmers and MSME actors, and documentation of activities. The results of the activities show that the construction of bore wells can increase planting intensity and agricultural productivity, while strengthening local food-based MSMEs has the potential to increase household income. The integration of these two programs contributes to improving food security, empowering the community economically, and promoting village independence.